Estimation of Flash Flood Properties Damage by Using GIS Spatial Analysis - Mohd Khusyairi Bin Kusmaniirat, Mohd Khusyairi (Universiti Teknologi Petronas, 2008)
The paper describes the use of spatial analysis on Geographical Information System(GIS) in analyzing the impact of flash flood to the properties damage. Flood is a natural disaster in this country and many other parts of the world.Flood damages/losses is essential to the flood victims for insurance claiming purposes. For the authorities ,it is also importance in order to decide whether the flood mitigation of the affected area is worth spending.